Specific Inhibition of Complement Activation Significantly Ameliorates Autoimmune Blistering Disease in Mice - Mihai, Sidonia; Hirose, Misa; Wang, Yi; Thurman, Joshua M.; Holers, V. Michael; Morgan, B. Paul; Köhl, Jörg; Zillikens, Detlef; Ludwig, Ralf J.; Nimmerjahn, Falk (Frontiers in Immunology, 2018)
Epidermolysis bullosa acquisita (EBA) is an autoimmune blistering disease characterized and caused by autoantibodies against type VII collagen (COL7). Transfer of antibodies against COL7 into mice induces a blistering disease dependent upon activation of complement component C5. Further, activation predominantly by the alternative pathway is required to elicit disease, as blistering was delayed and significantly reduced in factor B-/- mice. However, C5 deficiency not only prevented the downstream activation of terminal complement components with subsequent formation of the membrane attack complex (MAC), but also eliminated the production of C5a. Therefore, in the present study, we first aimed to elucidate which molecules downstream of C5 are relevant for blister formation in this EBA model and could be subsequently pharmaceutically targeted. For this purpose, we injected mice deficient in C5a receptor 1 (C5aR1) or C6 with antibodies to murine COL7. Importantly, C5ar1-/- mice were significantly protected from experimental EBA, demonstrating that C5a-C5aR1 interactions are critical intermediates linking pathogenic antibodies to tissue damage in this experimental model of EBA. In contrast, C6-/- mice developed widespread blistering disease, suggesting that MAC is dispensable for blister formation in this model. In further experiments, we tested the therapeutic potential of inhibitors of complement components which were identified to play a key role in this experimental model. Complement components C5, factor B and C5aR1 were specifically targeted using complement inhibitors both prophylactically and in mice that had already developed disease. All complement inhibitors led to a significant improvement of the blistering phenotype when injected shortly before anti-COL7 antibodies. To simulate a therapeutic intervention, anti-factor B treatment was first administered in full-blown EBA (day 5) and induced significant amelioration only in the final phase of disease evolution, suggesting that early intervention in disease development may be necessary to achieve higher efficacy. Anti-C5 treatment in incipient EBA (day 2) significantly ameliorated disease during the whole experiment. This finding is therapeutically relevant, since the humanized anti-C5 antibody eculizumab is already successfully used in patients. In conclusion, in this study, we have identified promising candidate molecules for complement-directed therapeutic intervention in EBA and related autoantibody-mediated diseases.